A history of consonance and dissonance - Tenney, James 1934-2006 (New York Excelsior Music Publishing Campany, 1988)
In music, a consonance is a harmony, chord, or interval considered stable, as opposed to a dissonance - considered unstable (or temporary, transitional). The strictest definition of consonance may be only those sounds which are pleasant, while the most general definition includes any sounds which are used freely.